2011
DOI: 10.1111/j.1467-8578.2011.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of school children with epilepsy: findings of a phenomenological study

Abstract: Epilepsy is one of the most frequently diagnosed neurological disorders among children. Epilepsy is continuously linked with academic underachievement and social challenges. Despite the implications that these difficulties have for a child's educational success, little is known of how children with epilepsy experience school. Understanding how to best support and accommodate these children can contribute to their positive adaptation and quality of life. The purpose of this phenomenological study by Jillian Rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 14 publications
0
45
0
1
Order By: Relevance
“…Disclosure of their child's epilepsy diagnosis to others is an important QoL issue, and source of stress and concern for parents. [20][21][22][23] However, prior to this study, limited evidence was available on parents' perspectives of navigating the disclosure decision-making process. This study offers unique insights into the challenges parents experienced when deciding to disclose the child's epilepsy diagnosis to others outside the family unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disclosure of their child's epilepsy diagnosis to others is an important QoL issue, and source of stress and concern for parents. [20][21][22][23] However, prior to this study, limited evidence was available on parents' perspectives of navigating the disclosure decision-making process. This study offers unique insights into the challenges parents experienced when deciding to disclose the child's epilepsy diagnosis to others outside the family unit.…”
Section: Discussionmentioning
confidence: 99%
“…A number of parents perceived non-disclosure as a protective mechanism to guard against their child experiencing what they viewed as unnecessary feelings of differentness, different treatment, restrictions, stigma and others' negative reactions. While parents' protective intentions for their child have been reported in prior research, [22][23][24][25][26][27][28] the consequences of parents concealing a child's epilepsy diagnosis has not been evaluated to any great extent.…”
Section: Discussionmentioning
confidence: 99%
“…, Amillategui et al . , Roberts & Whiting , Nurmi & Stieber‐Roger ). Pupils report feeling disappointed and frustrated with teachers' lack of knowledge, believing that school rules and teachers' attitudes limit their capacity to self‐manage their condition (Hayes‐Bohn et al .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is important to bear in mind that these evaluations were subjective as they involved perceptions of the families. When we look at the literature, several studies with families have demonstrated that teachers are not sufficiently educated about health problems such as chronic illnesses (Amillategui et al, 2007; Nurmi and Stieber-Roger, 2012; Roberts and Whiting, 2011). Many studies in the literature highlight that teachers need more knowledge about engaging with children with chronic health conditions (Clay et al, 2004; Mukherjee et al, 2000; Nabors et al, 2008).…”
Section: Discussionmentioning
confidence: 99%